Characterization of the Purchase Decision Process in the Category of Individual Life Insurance with Savings - González, Ensueño; Muñoz, Carolina; Robayo-Pinzon, Oscar; Rojas-Berrio, Sandra (International Journal of Industrial Engineering and Management, 2019)
This article’s goal is to describe the purchase decision process in the individual life insurance with savings category in Colombia. To this end, the attitudinal and behavioural characteristics of a sample of consumers that own life insurance policies with savings were identified. Given the objective of this report and its temporary scope, the design is of a non-experimental cross-sectional cut. The execution of the methodological strategy required qualitative instruments, and thus, its design was exploratory. Among the main results, it was found that the participants show a tendency to procrastinate, that the purchasing process has a high degree of complexity and that there are four associated factors: situational factors, individual factors, social factors and insurance company marketing activities factors. Key words Article history: Received (24-JAN-2019); Revised (15-AUG-2019); Accepted (5-OCT-2019); Published online (25-OCT-2019)